South-South Mutual Learning : A Priority for National Capacity Development in Africa - Assane Mayaki, Ibrahim (2012)
Evidence-based knowledge and innovation are critical for national development in Africa if the continent is to sustain the momentum of its transformation agenda. South- South Cooperation (SSC) is a mechanism that can contribute to this objective. Knowledge- and experience-sharing are taking place on different scales among African countries; but there is a need for coordination among these initiatives and with national development plans and processes. This will help scale up and institutionalize the practice of learning for development effectiveness as a capacity development tool.